Analisis Kelayakan Usaha Produk “Bakso Penyet CEMARA” - Mohamad Afrizal Miradji; Apriliana Laily Nurjannah; Ameliya Nur Indah; Sonya Sabrina Rossanti; Yohanes Gualbertus S; Regina Wijayanti; Afrian Tri Al Fanani; Amirotun Nisfih (Universitas Katolik Widya Karya Malang, 2023)
Feasibility study is an evaluation of the feasibility of a business that must be handled. A highly planned feasibility study must be able to know the benefits and risks of existing businesses or that will be carried out, knowing financial statements, marketing and promotional strategies, financial aspects, production processes, and sales targets. All business people, one of which is a meatball seller, must be able to provide innovation for their products in order to compete and continue to be in demand by consumers from various groups. Lately, the smashed meatballs with spicy chili business is one of the business ideas that is fairly modern among the public because this business has different concepts and innovation from meatballs that are generally soupy, so that these meatballs are created again into smashed meatballs that are served with rice, spicy chili, fermented soybean, and fresh vegetables.